CONTRASTIC STUDIES OF THE MAIN HEROIENES IN ENGLISH AND UZBEK LITERATURE (Multidisciplinary Journal of Science and Technology, 2025)
In this thesis provided a comparative analysis of the female characters who are the main characters of the scholar and writers and their works, which are prominent in English and Uzbek literary studies, as well as female characters who are well known to readers of their time in Uzbek literary science and, in a certain sense, were able to become a timeless type. Also, selected the characteristics of the female characters, both Western and Eastern, are similar and, in different ways, the aspects that have acquired universality are considered separately.